2020
DOI: 10.1099/jmm.0.001234
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and molecular characteristics of linezolid-resistant Staphylococcus capitis in Huashan Hospital, Shanghai

Abstract: Introduction. Linezolid-resistant (LZR) Staphylococcus capitis has recently emerged in our hospital, and its potential resistance mechanisms are still not clear. Aim. This study aimed to investigate the epidemiology, clinical and genetic characteristics, resistance mechanisms and biofilm formation capacity of LZR S. capiti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…In this study, the two linezolid-resistant isolates were both optrA-negative and poxtA-negative. These results were in partial agreement with Ding et al 25 who detected 21 linezolid-resistant staphylococcal isolated; 12 of them were positive for cfr, while all were optrA and poxtA negative.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the two linezolid-resistant isolates were both optrA-negative and poxtA-negative. These results were in partial agreement with Ding et al 25 who detected 21 linezolid-resistant staphylococcal isolated; 12 of them were positive for cfr, while all were optrA and poxtA negative.…”
Section: Discussionsupporting
confidence: 91%
“…Using breseq, we mapped the genome reads to the 23S rRNA reference sequence and calculated the mutation proportion of each base. The mutation detection result indicated that the L clone is characterized by multiple copies of C2576G and C2104T mutations, in accordance with the findings of a previous study 17 . Based on this evidence, we inferred that the L clone might have been previously exposed to anti-ribosomal drugs such as linezolid or florfenicol, which are often used in the ICU.…”
Section: Discussionsupporting
confidence: 91%
“…To evaluate the applicability of the S. capitis cgMLST scheme for outbreak analysis, we reanalyzed the published genomic data of S. capitis isolates from an outbreak in Shanghai 17 and another independent outbreak in Sir Run Run Shaw Hospital in Hangzhou as well as two sporadic cases, one in Harbin and one in Hangzhou. All genomes included are listed in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, linezolid-resistant clones have been described in adult ICUs in Europe [4] and in China. [5] Further investigation is required to determine whether the linezolid-resistant S. capitis isolates in the Western Cape and other provinces are clonally related or not, and to elucidate the underlying mechanism(s) of resistance.…”
Section: Increase In Linezolid Resistance In Staphylococci In the Private Sector In Western Cape Province South Africamentioning
confidence: 99%